2016
DOI: 10.14214/sf.1663
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of genetic diversity in <i>Fagus sylvatica</i> at the north-eastern edge of the natural range

Abstract: Distribution of genetic diversity in Fagus sylvatica at the north-eastern edge of the natural rangeKempf M., Konnert M. (2016). Distribution of genetic diversity in Fagus sylvatica at the north-eastern edge of the natural range. Silva Fennica vol. 50 no. 4 article id 1663. 17 p. http://dx.doi.org/10.14214/sf.1663. Highlights• European beech at the north-eastern edge of its natural range in Poland have a high level of genetic variation, similar to the populations from Central Europe.• The differences between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
4
8
0
Order By: Relevance
“…These differences might obviously result from the fact that we sampled only a single population, located in the north-eastern distribution limit, presumably in the front edge of an expanding population (Magri et al, 2006). However, similar levels of genetic diversity, as in our study, were found in other beech populations (Westergren et al, 2015;Kempf and Konnert, 2016).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These differences might obviously result from the fact that we sampled only a single population, located in the north-eastern distribution limit, presumably in the front edge of an expanding population (Magri et al, 2006). However, similar levels of genetic diversity, as in our study, were found in other beech populations (Westergren et al, 2015;Kempf and Konnert, 2016).…”
Section: Discussionsupporting
confidence: 55%
“…Elevated levels of inbreeding in beech were found in several studies (Vornam et al, 2004;Buiteveld et al, 2007;Paffetti et al, 2012), but in most cases it was a likely effect of the presence of null alleles. Other authors (Rajendra et al, 2014;Westergren et al, 2015;Kempf and Konnert, 2016) observed relatively low levels of inbreeding. Apparently, when F is is estimated along with accounting for the presence of null alleles, the levels of inbreeding in beech are usually found to be insignificant (Piotti et al, 2013;Pluess and Maattanen, 2013).…”
Section: Discussionmentioning
confidence: 90%
“…This general genetic pattern was similar for European beech in almost all European regions as demonstrated mainly by isozyme studies (see Comps et al 1990, Gömöry et al 1992, Hazler et al 1997, Konnert 1995, Leonardi & Menozzi 1995, Merzeau et al 1994. For nSSR markers only few studies on genetic variability of beech populations exist (see Vornam et al 2004, Buiteveld et al 2007, Ciocîrlan 2014, Ciocîrlan et al 2017, Lander et al 2011, Liesebach et al 2015, Kempf & Konnert 2016. Szasz-Len (2016) conducted a PCoA and STRUCTURE analysis with the presented 10 populations from Romania and 16 European beech populations from Germany and Bulgaria.…”
Section: Discussionmentioning
confidence: 70%
“…Abbreviations: Df -degree of freedom; SS -sum of squares; MS -mean sum of squares; P -probability. zygosity of the investigated populations was related to populations of Fagus sylvatica from Central Europe (Vornam et al 2004, Dounavi et al 2016, Kempf & Konnert 2016, even if partially different markers were used and a direct comparison of results is difficult. Thus for example for 13 beech populations in the marginal and core areas of beech distribution in Romania Ciocîrlan (2014) based on eight nuclear microsatellites calculated a mean observed heterozygosity of 0.651, whereas the overall expected heterozygosity was 0.703.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no reduced genetic diversity was detected in leading edge populations of Castanopsis sclerophylla (Lindl. and Paxon) Schottky in China (Shi & Chen ), in F. sylvatica at its north‐eastern natural distribution limit (Kempf & Konnert ), as well as at the rear edge of the species range (Bontemps et al . ) and in Quercus ilex L. populations growing at the northern distribution limit of the species (Vernesi et al .…”
Section: Genetic Diversitymentioning
confidence: 99%